Twin-to-Twin Transfusion Syndrome: A Comprehensive Review of Fetal Impact and Management Strategies - Mikusek, Wiktoria; Patelski, Mikołaj; Czapla, Maciej; Surma, Mateusz; Molenda, Jakub; Kuczma, Matylda; Kotlarz, Wiktoria; Kamińska, Marta; Klimczak, Adrianna; Pietrzak, Barbara (Quality in Sport, 2026)
Introduction Twin-to-Twin Transfusion Syndrome (TTTS) affects 10–15% of monochorionic diamniotic twin pregnancies and arises from unbalanced blood flow through placental vascular anastomoses. The presence of deep arteriovenous connections leads to chronic transfusion from one twin to the other, resulting in progressive hemodynamic imbalance. Without timely intervention, TTTS poses a high risk of fetal morbidity and mortality. Aim of the study The aim of this review was to present an up-to-date overview of current knowledge, clinical approaches, and fetal implications related to Twin-to-Twin Transfusion Syndrome. Materials and methods A structured literature search was performed in PubMed and Google Scholar to identify studies on Twin-to-Twin Transfusion Syndrome, focusing on management and fetal outcomes. The search included relevant keywords and Medical Subject Headings (MeSH). Additional studies were identified through manual screening of reference lists. Conclusion Twin-to-Twin Transfusion Syndrome (TTTS) is a severe complication of monochorionic twin pregnancies that requires early diagnosis and active management. Fetoscopic laser photocoagulation (FLP) remains the gold standard treatment, significantly improving survival. Despite therapeutic advances, affected fetuses still face risks of neurological and cardiac complications, highlighting the importance of long-term follow-up.